E-Voting Berbasis Website Pada Pemilihan Kades Di Rantau Jaya (Lake) Dengan Keamanan Data Menggunakan Enkripsi Base 64 - Harma Oktafia Lingga Wijaya (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The world of technology and science at this time is growing rapidly, resulting in many changes that occur in human life. Thus, with the development of this technology every work will be realized more efficiently and effectively. Information Systems made to facilitate the management and storage of data it can produce a precise and accurate information. Currently a form of information and data can be made in accordance with what we want, and many opportunities that can be exploited to develop it. From the above information, to overcome perkembanagn existing technology it is necessary to create a website-based information system, is expected to facilitate the delivery of information and minimize fraud, e-voting refers to the process of utilization of electronic devices to further support the smooth process and also the automation model that allows intervention At least from individuals in all processes. The electoral system in this village still uses the conventional electoral system, the voting process and the vote count in the conventional election are still many weaknesses among them is the wrong voters in terms of marking on the ballot paper, because the provisions of the validity of the marking is less clear that many sound cards are in And the second is on the announcement of the results of the slow election because it must perform calculations manually and often fraud, and data equality is very important in this system because the election is a crucial problem in the community so that the necessary security of data election results tersebut.maka in The data security researchers use base 64 encryption.